Active power fluctuations and control in hydraulic disturbance of variable speed pumped storage plants. (April 2023) - Huang, Yifan; Yang, Weijia; Zhao, Zhigao; Yang, Jiandong
Abstract: Variable-speed pumped-storage unit (VSPSU) is state-of-the-art technology and has appeared as a new orientation of the world pumped-storage industry in recent years, but the dynamic performance of VSPSU under hydraulic disturbance has yet to be developed. The hydraulic disturbance means that normally operating pumped-storage units are inevitably affected by sudden operation changes of other units in the same waterway system. It is an important working condition in transient simulations of pumped-storage plants. In this study, a nonlinear model of a VSPSP containing multiple units is established based in MATLAB/Simulink, integrating hydraulic, mechanical, and electrical subsystems. The model is validated through comparison with on-site experiments. The fast power control strategy is adopted, enabling the unit to follow the power command rapidly and stably. The simulations show that VSPSU outperforms fixed-speed pumped-storage unit (FSPSU) in mitigating active power fluctuations under hydraulic disturbance. But VSPSU still faces active power fluctuations. This phenomenon is induced by the effect of the speed pulling-back control, which is used to keep the unit speed within the allowable speed variation range. Factors that influence the active power fluctuations are analyzed, and a useful countermeasure is proposed to solve active power fluctuations. The findings in this paper could provide understanding and guidance for the practical operation of VSPSUs. Highlights: Building a pumped storage plant model in which multiple units share one waterway. Comparing the dynamic performance of VSPSU and FSPSU under hydraulic disturbance. Explaining the reasons for power fluctuations of VSPSU under hydraulic disturbance. Proposing a suitable approach to solve the active power fluctuations of VSPSU.